Decision-making Criteria in Angel Investing: Analysis of Lived Experiences of Negotiations between Entrepreneurs and Angel Investors - Almubarak, Norah; AlShayeb, Sarah; AlAsmakh, Zahra; AlMinhali, Amirah (Jordan Journal of Business Administration, 2025)
The aim of this research is to determine and analyze the criteria that influence the decisions made by angel investors when investing. The authors conducted their research by observing and analyzing live negotiations between entrepreneurs and angel investors during business pitch competitions featured on the TV show Hawamir Challenge Program. The Gioia method was used to analyze the collected data. The authors identified 23 criteria, which were categorized into 7 categories related to entrepreneur/team, presentation, product/service, market, financial factors, community impact, and investor characteristics. The research contribution of this study is significant, because it utilized real-life experiences of negotiations between entrepreneurs and angel investors, which provided valuable insights into the actual experiences of the parties involved. Therefore, the research can help entrepreneurs increase their chances of securing investment by providing them with the knowledge, ththey need to prepare before entering into negotiations with angel investors.